Low activity of select Hsp104 mutants is sufficient to propagate unstable prion variants - Dulle, Jennifer E (Landes Bioscience, 2013)
The molecular chaperone network plays a critical role in the formation and propagation of self-replicating yeast prions. Not only do individual prions differ in their requirements for certain chaperones, but structural variants of the same prion can also display distinct dependences on the chaperone machinery, specifically Hsp104. The AAA+ ATPase Hsp104 is a disaggregase required for the maintenance of most known yeast prions. As a key component in the propagation of prions, understanding how Hsp104 differs in its interaction with specific variants is crucial to understanding how prion variants may be selected or evolve. Here, we investigate two novel mutations in Hsp104, hsp104-G254D, and hsp104-G730D, which allow us to elucidate some mechanistic features of Hsp104 disaggregation and its requirement for activity in propagating specific prion variants. Both Hsp104 mutants propagate the [PSI+] prion to some extent, but show a high rate of prion loss. Both Hsp104-G254D and Hsp104-G730D display reduced biochemical activity, yet differ in their ability to efficiently resolubilize disordered, heat-aggregated substrates. Additionally, both mutants impair weak [PSI+] propagation, but are capable of propagating the less stable strong [PSI+] variant to some extent. One of the Hsp104 mutants also has the ability to propagate one variant of the [RNQ+] prion. Thus, our data suggest that changes in Hsp104 activity limit substrate disaggregation in a manner that depends more on the stability of the substrate than the nature of the aggregated species.